Diagnóstico de la situación de la mujer campesina en Colombia (2017)
Although the role of rural women in the performance of the economy is fundamental, their situation has been lagging behind in domestic work without recognizing the importance of their work, but rather, on the contrary, discriminating their performance and chaining it in a circle of poverty that also includes the family unit on which she depends. In the present work an analysis is made of the current situation of women in the Colombian countryside, making a comparison between genders to identify the state of their sustainable livelihoods, that is, assets they can access, and how they influence in its poverty situation, for this, the data of the third national agricultural census are used